1976
DOI: 10.3382/ps.0550229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Texture Profile for Cooked Chicken Breast Meat by Principal Component Analysis

Abstract: During a profiling stage five subjects were asked to describe as completely as possible their textural impressions following the consumption of cooked chicken breast halves. This resulted in a group decision for seven descriptive terms in dutch: hardheid (hardness), samenhangendheid (cohesiveness), elasticiteit (elasticity), droogheid (dryness), vettigheid (fattiness), stroefheid (roughness) and kauwbaarheid (chewiness). Next the subjects were asked to judge these attributes from 66 breast halves (from 33 chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Horsfield and Taylor (1976) found a relationship between juiciness and the structural-mechanical elements of fiber breakdown and the nonuniformity of texture. Frijters (1976) and Dransfield et al (1984) found juiciness to be a separate, but principal, component of texture profiles for cooked meats.…”
Section: Sensory Data Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Horsfield and Taylor (1976) found a relationship between juiciness and the structural-mechanical elements of fiber breakdown and the nonuniformity of texture. Frijters (1976) and Dransfield et al (1984) found juiciness to be a separate, but principal, component of texture profiles for cooked meats.…”
Section: Sensory Data Resultsmentioning
confidence: 95%
“…Other researchers, using different but related terms for texture, found similar results in search of a simpler structure to explain sensory texture. Frijters (1976) concluded that texture assessment could be grouped into three factors: mechanical (hardness, cohesiveness, elasticity, chewiness); fluidity (dryness, roughness); and fattiness. Dransfield et al (1984) reduced nine attributes to two principal components (mechanical and the juicy residue) but concluded that at least five attributes should be retained for sensory testing in order to evaluate cooked meats: toughness, connective tissue, fiber close-ness, residue, and juiciness.…”
Section: Sensory Data Resultsmentioning
confidence: 99%
“…Univariate techniques are used when dealing with one attribute, but multivariate approaches often provide a much clearer picture when handling several attributes. Techniques, such as principal component, principal co-ordinate and discriminant analysis (Clapperton & Piggott , 1979;Frijters, 1976;Pangborn, 1981;Williams, 1981;Williams et al, (in press)) can also be applied to determine underlying dimensions, but for determination of the significance of any difference it is necessary to resort to multivariate analysis of variance or canonical vanate analysis (Vuataz, 1976/77), Multivariate techniques, in general, allow one to examine the spatial distribution of scores given to attributes, selecting orthogonal axes through this space which satisfy certain criteria, i.e. accounting for maximum variation in the case of principal component or co-ordinate analysis, or maximum discrimination in the case of discriminant or canonical variate analysis.…”
Section: Interpreting Results From Scored Datamentioning
confidence: 99%
“…Previous studies of the texture of carcass meats (Harries et a/ 1972;Frijters 1976;Dransfield et a/ 1984) and meat products such as frankfurters (Syarief et a/ 1985) and burgers have shown that the major source of variation derives from mechanical attributes describing the initial stages of mastication. A similar result was found here, where 'initial firmness', 'skin toughness' and 'meatiness' comprised the toughness/tenderness component.…”
Section: Sensory Components Of Sausage Qualitymentioning
confidence: 99%
“…On the first principal sensory axis, the relationship between 'skin toughness', 'firmness', 'meatiness', puncture and compressive strengths suggests a toughness/ tenderness component in common with other meats (Harries et al 1972;Frijters 1976;Dransfield et a/ 1984. Nitrogen was the only proximate constituent relating to this axis, and as an approximate measure of lean meat content it shows that sausages with more lean meat were tougher, firmer and stiffer and stronger under compression.…”
Section: Sensory and Instrumental Relationshipsmentioning
confidence: 99%